1993
DOI: 10.1056/nejm199301213280305
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tocopherol and Deprenyl on the Progression of Disability in Early Parkinson's Disease

Abstract: Deprenyl (10 mg per day) but not tocopherol (2000 IU per day) delays the onset of disability associated with early, otherwise untreated Parkinson's disease. The action of deprenyl that accounts for its beneficial effects remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
156
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,075 publications
(158 citation statements)
references
References 27 publications
2
156
0
Order By: Relevance
“…These outcomes include time to initiation of ST, time to the development of motor complications, use of ST and nonmotor disability. Time to initiation of ST has been a primary outcome in several completed studies that examined the efficacy of putative disease‐modifying interventions 5, 29. Although it has been criticized for the subjective nature of the measure and being impacted by the change in the treatment algorithms that overall lead to the earlier initiation of ST, nevertheless it can be considered a surrogate measure of the disease progression and allows us to compare our findings with previous trials.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…These outcomes include time to initiation of ST, time to the development of motor complications, use of ST and nonmotor disability. Time to initiation of ST has been a primary outcome in several completed studies that examined the efficacy of putative disease‐modifying interventions 5, 29. Although it has been criticized for the subjective nature of the measure and being impacted by the change in the treatment algorithms that overall lead to the earlier initiation of ST, nevertheless it can be considered a surrogate measure of the disease progression and allows us to compare our findings with previous trials.…”
Section: Discussionmentioning
confidence: 98%
“…We also considered a prolonged wash out at the end of study or at the time of initiation of ST to reassess for the evidence of symptomatic benefit, but there are strong arguments against such design, including lack of obvious symptomatic effect of isradipine in our Phase II STEADY‐PD2 study and participant burden. In addition, there is no consensus regarding the necessary duration of the washout that would be required for isradipine 5, 28. Therefore, our design represents the most rational approach to study the efficacy of isradipine on disability in PD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The DATATOP study22 found that the use of selegiline delays the need for levodopa in early PD, but most investigators have interpreted this as a symptomatic effect caused by MAO‐B inhibition that delays dopaminergic elimination from dopaminergic synapses. However, two randomized double‐blind long‐term Scandinavian studies comparing selegiline to levodopa in early PD found that patients receiving placebo needed progressively higher doses of levodopa than patients receiving selegiline 23, 24.…”
Section: Initial Treatmentmentioning
confidence: 99%